Risk of Venous Thromboembolic Complications in Patients with Atrial Fibrillation: a Systematic Review and Meta-analysis - A. A. Sokolova; A. A. Kudriavtseva; N. V. Kostokova; M. P. Zaikina; Z. A. Gebekova; D. A. Napalkov; I. A. Zolotukhin (Рациональная фармакотерапия в кардиологии, 2022)
Aim: The aim of this meta-analysis and systematic review was to evaluate the possible connection between AF and VTE.Material and methods. Atrial fibrillation (AF) and atrial flutter (AFL) contribute to intra-atrial blood stasis which leads to thrombus formation with its embolization. There is some evidence that AF can be a risk factor for deep vein thrombosis (DVT) and pulmonary embolism (PE). The following databases were searched: PubMed (MEDLINE), EMBASE, Google Scholar, the Cochrane Central Register of Controlled Trials. The time frame for conducting a systematic literature search ranged from January 1, 1990 to November 1, 2021. The diagnosis of atrial fibrillation had to be confirmed by using ECG. The diagnosis of VTE could be made with Doppler imaging, ventilation/perfusion scan, CT angiography, venography, angiography or autopsy. Only the three studies with 102192 patients meeting the requirement were included in the meta-analysis.Results. The prevalence of DVT and PE were assessed using incidence rate ratios (IRR) method of the inverse variance random effects model and its 95% confidence interval (CI). The significant association between atrial fibrillation and pulmonary embolism was found (IRR, 4.18 95% Cl 1.958.98). Also there is obvious association between DVT and AF (IRR, 2.97 95% Cl 2.18-4.03).Conclusion. It can be concluded that the increased risk of developing VTE is associatedwith concomitant AF.